STUDI EKSPERIMEN: PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KETERAMPILAN PROSES SAINS SISWA SMP - Wa Ode Siti Hamsinah Day; Hariani Fitriani; Retno Wuri Sulistyowati (Program Studi PGSD Universitas Flores, 2023)
Science learning focuses on students' direct experience through scientific activities. The purpose of this study was to determine the effect of problem-based learning (PBL) and guided inquiry learning model (GIL) on science process skills (SPS) in science subjects in class VII SMP Negeri 14 Kendari. The research method used is quasi-experimental. The PBM model is taught in the experimental class, namely class VII with 34 students and the PIT model is taught in class VII with 35 students. KPS data collection techniques through observation during the implementation of learning. Data analysis using SPSS with independent sample t test. The results of data analysis showed tcount = 28,628 > ttable = 1.996, so it can be said that the PBM model students had a significant effect compared to the PIT model on the science process skills of class VII SMP Negeri 14 Kendari.